2021
DOI: 10.36253/rief-10179
|View full text |Cite
|
Sign up to set email alerts
|

Vécu de familles monoparentales avec jeunes enfants durant le premier confinement lié à la COVID-19 en France

Abstract: En France, comme dans de nombreux pays, les mesures imposées lors de la pandémie de COVID-19 ont bouleversé le vécu des familles. Parmi elles, le vécu des familles monoparentales avec jeunes enfants semble singulier. L’article réside dans l’analyse des réponses à un questionnaire en ligne diffusé pendant le premier confinement, auquel certains de ces foyers se sont soumis, en mettant en perspective le vécu exprimé et les conditions de vie. Les données confirment une situation de plus grande fragilité de ces fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…While in our study parents of children with developmental disorders have used social distancing measures considerably more than parents in the control population, we have also shown that single-parent families in our study have paid greater attention to protective measures (aside from social distancing rules; Moscaritolo et al, 2021 ). In both cases, these elements attest to additional worry and fear regarding the risk of contracting the virus in households where the parents’ presence is more than necessary when rehabilitation and care institutions are closed.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…While in our study parents of children with developmental disorders have used social distancing measures considerably more than parents in the control population, we have also shown that single-parent families in our study have paid greater attention to protective measures (aside from social distancing rules; Moscaritolo et al, 2021 ). In both cases, these elements attest to additional worry and fear regarding the risk of contracting the virus in households where the parents’ presence is more than necessary when rehabilitation and care institutions are closed.…”
Section: Discussionmentioning
confidence: 61%
“…Our hypothesis regarding the increased difficulties encountered was, however, not entirely confirmed. Indeed, similarly to single-parent households ( Moscaritolo et al, 2021 ), only resourcing difficulties came on top of health issues (other than COVID), suggesting an additional burden for the most vulnerable families. Other difficulties (noise, tensions, lack of space, etc.)…”
Section: Discussionmentioning
confidence: 99%